Síntese de proteína microbiana, metabolismo de nitrogênio e perdas endógenas em caprinos suplementados no semiárido - Costa, Izabelle Crystine Almeida (2021)
The objective was to estimate microbial protein synthesis using the purine derivative method, to evaluate blood and urinary nitrogen metabolism, nitrogen balance and endogenous protein losses by NRC (2007) and AFRC (1993) in supplemented goats with leguminous hays associated or not with small forage palm in the Semiarid region. The experiment was carried out at the Rural Technology Development and Dissemination Station of the backcountry of Alagoas located in the city of Piranhas-AL. Thirty male goats, castrated, without defined breed standard (SPRD), with initial average weight of ± 15 kg were used. The experimental period lasted 105 days, divided into five sub-periods of 21 days each, aiming at adjusting the supplementation. Supplementation was based on 1% of body weight in dry matter. The treatments were: PA = grazing at will without supplementation; LEU = leucena hay (Leucaena leucocephala (Lam) de Wit.); LEU + P = leucena hay + forage palm (Nopalea cochenillifera - Salm Dyck); SAB = sabia hay (Mimosa caesalpiniifolia Benth); and SAB + P = sabia hay + small forage palm. Stool collections were made directly from the rectal ampoule using the LIPE indicator, to estimate dry matter consumption and for fecal nitrogen analysis. Spot urine and blood samples were collected after four hours of supplementation, for analysis of total nitrogen, creatinine and purine derivatives in the urine (hypoxanthine, xanthine, uric acid and allantoin), urea and urinary nitrogen, urea and plasma nitrogen. Endogenous losses were obtained using the equations of the NRC (2007) and AFRC (1993). The design used was completely randomized, with five treatments and six repetitions. And the statistical program used for statistical analysis was R (2019). Purine derivatives and, consequently, absorbed purines, nitrogen and microbial protein showed a significant difference (P <0.05) between treatments, with the highest averages being found in supplements with leucena hay associated or not with small palm. However, treatments with sabia hay presented lower averages for the respective variables. The urea and plasma nitrogen showed a significant difference (P <0.05) between the treatments, with higher values for the treatment with leucena hay and saiba hay. Urea and urea nitrogen did not show any significant difference (P> 0.05). The nitrogen balance was positive for all treatments, with higher averages when leucena hay and leucena hay + palm were used. The endogenous losses estimated by the NRC (2007) were higher than those estimated by the AFRC (1993) with higher absolute values for the treatments leucena hay, leucena hay + palm and sabia hay + palm . However, it is feasible to supplement leguminous plants associated or not with forage palm in the feeding of goats in the Semiarid region.